Implementasi Program Intervensi Gizi Terhadap Penurunan Stunting di Desa Tambak Kalisogo, Kecamatan Jabon, Kabupaten Sidoarjo - Julia Eka Cesar Suwanti; Lailul Mursyidah (STISIPOL Raja Haji, 2026)
Stunting remains high in rural coastal areas despite routine nutrition intervention programs, highlighting a gap between policy objectives and local outcomes. This study aims to analyze the implementation of the Nutrition Intervention Program in Tambak Kalisogo Village, Sidoarjo, using (Dwiyanto, 2005) framework: goal clarity, organizational capacity, coordination, accountability, and community participation. A descriptive qualitative method was applied through interviews, observations, and documentation involving village officials, midwives, posyandu cadres, and parents of stunted toddlers. The results show that program execution complies with technical procedures but remains suboptimal in significantly reducing stunting rates. Primary obstacles include limited cadre capacity, administrative-focused coordination, underutilized e-PPGBM data, and community participation that fails to foster dietary behavioral changes. Overall, program implementation focuses heavily on activity outputs rather than sustainable outcomes. Strengthening implementer capacity, integrating cross-sector coordination, and empowering communities are essential to enhance program effectiveness.